The role of the interleukin-36 axis in generalized pustular psoriasis: a review of the mechanism of action of spesolimab - Hawkes, Jason E.; Visvanathan, Sudha; Krueger, James G. (Frontiers in Immunology, 2023)
Generalized pustular psoriasis (GPP) is a rare, chronic, inflammatory skin disorder characterized by recurrent flares associated with skin erythema, desquamation, and widespread superficial sterile pustules, which may be severe (“lakes of pus”). Systemic symptoms are often present, including malaise, fever, and skin pain. In GPP, innate immune responses are driven by abnormal activation of the interleukin (IL)-36-chemokine-neutrophil axis and excessive neutrophil infiltration. This review highlights the IL-36 pathway in the context of the IL-1 superfamily and describes how unopposed IL-36 signaling can lead to the development of GPP. Targeted inhibition of the IL-36 receptor (IL-36R) is an attractive therapeutic strategy in the treatment of GPP, including flare prevention and sustained disease control. Spesolimab is a first-in-class, humanized, monoclonal antibody that binds specifically to the IL-36R and antagonizes IL-36 signaling. Spesolimab was approved by the US Food and Drug Administration in September 2022 to treat GPP flares in adults and was subsequently approved for GPP flare treatment in other countries across the world. Anti-IL-36R therapy, such as spesolimab, can mitigate flares and address flare prevention in GPP, presumably through rebalancing IL-36 signaling and modulating the pro-inflammatory response of the downstream effectors.